Evaluate the sum: n = 2 ∑ 2 0 2 1 n ( n − 1 ) 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thank you Sir for sharing your solution.
n = 2 ∑ 2 0 2 1 ( n − 1 ) ( n ) 1 = 1 − 2 0 2 1 1 = 2 0 2 1 2 0 2 0
We can write the first few terms to see how terms get cancelled:
1 × 2 1 = 1 − 2 1
2 × 3 1 = 6 1 = 2 1 − 3 1
3 × 4 1 = 1 2 1 = 3 1 − 4 1
e t c . . .
n = 2 ∑ 2 0 2 1 ( n − 1 ) ( n ) 1 = ( 1 − 2 1 ) + ( 2 1 − 3 1 ) + ( 3 1 − 4 1 ) + ⋯ + ( 2 0 2 0 1 − 2 0 2 1 1 ) = 1 − 2 0 2 1 1 = 2 0 2 1 2 0 2 0
Problem Loading...
Note Loading...
Set Loading...
n = 2 ∑ 2 0 2 1 n ( n − 1 ) 1 = n = 1 ∑ 2 0 2 0 n ( n + 1 ) 1 = n = 1 ∑ 2 0 2 0 ( n 1 − n + 1 1 ) = 1 1 − 2 1 + 2 1 − 3 1 + 3 1 − 4 1 + 4 1 − ⋯ − 2 0 2 0 1 + 2 0 2 0 1 − 2 0 2 1 1 = 1 − 2 0 2 1 1 = 2 0 2 1 2 0 2 0 By partial fraction decomposition